PORTOFOLIO PROFIL KONDISI FISIK MAHASISWA PJKR UNWAHAS SEMESTER GASAL 2022-2023 - Catur Wahyu Priyanto; Muhlisin; Sudarwati; Tohir; Muhammad Faza Zidni Mubarok (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2023)
In this study the aim was to determine the profile level of a student's physical condition based on the portfolio of each student in the Health and Recreation Physical Education Study Program at Wahid Hasyim University. The object of research in this study was limited to students of the Physical Health and Recreation Education Study Program Class of 2020, 2021 and 2022 at Wahid Hasyim University. The population in this study were 240 students and the sample used was 90 samples, by means of taking using random sampling technique. This research is a descriptive quantitative research. The method used is a survey with test and measurement techniques. In this study the instruments used were 9 physical condition test items including: Circulatory and Respiratory Endurance, Muscle Strength, Speed, Explosiveness, Flexibility, Agility, Coordination, Balance, Reaction Speed. The conclusion of this research is that 9 students are in very good category, 19 students are in good category, 35 students are in sufficient category, 24 students are in poor category, 3 students are in very poor category